DIFFERENCES IN SQUID ATTRACTOR MATERIALS AND THEIR INFLUENCES ON THE EFFECTIVENESS OF SQUID EGG ATTACHMENT - Alhusna, Indra Sundara; Mawardi, Wazir; Purwangka, Fis; Yusfiandayani, Roza (Departemen PSP IPB, 2025)
The criteria for strength and durability of construction are critical in connection with the addition of coral fragments that add to the load on the squid attractor. The two materials to be tested are PVC and bamboo pipe materials based on adding fragments or without coral fragments. This study aims to compare the effectiveness of squid attractors made of bamboo with PVC pipes as a means of developing artificial habitats for another aquatic biota with the following points, namely, examining the influence of materials and the presence of coral fragments on the effectiveness of squid attraction, knowing the presence of fish and another biota in squid attractors made of bamboo and PVC pipes as well as the quality of seawater that supports the presence of fish and marine life and tests the resistance of hydrodynamic forces of squid attractors, bamboo materials and PVC pipes aligned with coral fragment planting. The analysis methods used include the effectiveness of squid attractor, fish abundance analysis, determination of squid attractor construction based on hydrodynamic forces, normality test, and statistical test (T-test/ Wilcoxon Test). The effectiveness of bamboo and PVC squid attractors with the addition of coral fragments and without coral fragments has very effective results. The use of bamboo squid attractors with the addition of coral fragments has a more significant abundance value. The addition of coral fragments increases stability to withstand hydrodynamic forces. Key words: squid attractor, bamboo, coral fragments, PVC